Analisis Peran Dewan Pengawas Syariah (DPS) dalam Mengawasi Perusahaan Asuransi Syariah - Siti Khoiriyah Karina Ujung; Zainarti Zainarti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The function of the Sharia Supervisory Board (DPS) in overseeing Indonesian sharia insurance providers is examined in this study. This study examines how DPS fulfills its responsibilities to guarantee adherence to sharia principles in insurance operations and products using qualitative approaches based on a review of the literature. As a supervisor and advisor in sharia financial institutions, DPS is crucial. However, because of a lack of expertise in the sharia insurance industry and a shortage of human resources, DPS performance is still subpar, according to this study. The analysis's findings highlight how crucial it is to improve DPS's role and capabilities through pertinent education and training in order to boost the effectiveness of sharia supervision in the insurance industry.